2018
DOI: 10.3390/ma11040580
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Electrospun Polycaprolactone Scaffold Functionalized with Ibuprofen for Periodontal Regeneration: An In Vitro andIn Vivo Study

Abstract: Ibuprofen (IBU) has been shown to improve periodontal treatment outcomes. The aim of this study was to develop a new anti-inflammatory scaffold by functionalizing an electrospun nanofibrous poly-ε-caprolactone membrane with IBU (IBU-PCL) and to evaluate its impact on periodontal inflammation, wound healing and regeneration in vitro and in vivo. IBU-PCL was synthesized through electrospinning. The effects of IBU-PCL on the proliferation and migration of epithelial cells (EC) and fibroblasts (FB) exposed to Porp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 74 publications
2
52
0
Order By: Relevance
“…Furthermore, several studies have indicated the effect of the host response on the periodontium by blocking and modulating periodontal disease development. 26 In the present study, the changes in periodontal parameters after subgingival irrigation with ibuprofen led to a significant reduction in bleeding on probing at baseline and after 15,30,45,60,75, and 90 days.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, several studies have indicated the effect of the host response on the periodontium by blocking and modulating periodontal disease development. 26 In the present study, the changes in periodontal parameters after subgingival irrigation with ibuprofen led to a significant reduction in bleeding on probing at baseline and after 15,30,45,60,75, and 90 days.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, another study showed that electrospun polycaprolactone scaffold functionalized with ibuprofen significantly improved the clinical attachment, reduced inflammation-induced bone loss, efficiently and differentially controlled inflammatory and migratory gingival cell reaction, and probably promoted periodontal regeneration. 60 That is why topical use is a valid alternative for completing the treatment of periodontal disease. Local forms used in dentistry involve mouthrinses, supra-and subgingival irrigation, and subgingival devices.…”
Section: Discussionmentioning
confidence: 99%
“…To date, polymeric EFs have been used in several biomedical applications including wound dressing materials (Liu et al, 2017), tissue regeneration (Inanç et al, 2009;Yang et al, 2009), and as drug delivery vehicles for bioactive molecules, antimicrobial agents (Chaturvedi et al, 2013), anti-inflammatory drugs (Batool et al, 2018), and anesthetics (Zafar et al, 2016). For periodontal applications, PLGA fibers have acted as cell scaffolds (Inanç et al, 2009), and have been combined with other polymers including PCL and PLA to deliver traditional antibiotics such as doxycycline (Chaturvedi et al, 2013) and metronidazole for the localized treatment of periodontitis (Zamani et al, 2010;Reise et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, a delivery system, such as fibers, that can facilitate ease of administration, while localizing doses applied directly to the subgingival pocket or as topically administered dental strips, may be one option to improve efficacy and overcome toxicity challenges associated with high dose and repeated administrations. To meet these needs, both nondegradable and lesser studied degradable vehicles have been developed for the delivery of antibiotics as primary or adjunct therapies and some are commercially available (Friesen et al, 2002;Kenawy el et al, 2002;Ahuja et al, 2003;Aimetti et al, 2004;Kim et al, 2004;Zamani et al, 2010;Batool et al, 2018). However, the utilization of non-biodegradable vehicles requires surgical removal, which can increase the risk of infection and foreign body response (Vyas et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To date, polymeric EFs have been used as delivery vehicles in several biomedical applications including wound dressing materials 158 , tissue regeneration 159,160 , and as drug delivery vehicles for bioactive molecules, antimicrobial agents 97 , anti-inflammatory drugs 170 , and anesthetics 171 . Moreover PLGA fibers have provided cell scaffolds 160 , and have been combined with other polymers including PCL and PLA to deliver traditional antibiotics such as doxycycline 97 and metronidazole for the localized treatment of periodontitis 98,172 .…”
Section: Discussionmentioning
confidence: 99%